Severe Symptomatic Epidural Hematoma Following Percutaneous Endoscopic Unilateral Laminectomy for Bilateral Decompression (Endo‐ULBD)—Series Report and Management Strategies - Antao Lin; Shengwei Meng; Chao Wang; Xiaodan Zhao; Shuo Han; Hao Zhang; Yanqing Shen; Kai Zhu; Dan Zhou; Kunpeng Su; Xuexiao Ma; Chuanli Zhou (Orthopaedic Surgery, 2023)
Objectives Severe symptomatic epidural hematoma (SSEH) is one of the most severe complications following percutaneous endoscopic unilateral laminectomy for bilateral decompression (Endo‐ULBD). Considering that this technique has been performed for a short time, no detailed reports have been recently published. Thus, it is critical to gain a better understanding of SSEH occurring in its postoperative period with regard to its incidence, possible causes, outcome, etc., in order to identify relevant management strategies. Methods Patients with spinal stenosis who had undergone Endo‐ULBD in our department from May 2019 to May 2022 were retrospectively analyzed. Of which, patients with postoperative epidural hematoma were followed‐up. The preoperative and postoperative physical conditions of each patient were recorded, and the information related to hematoma removal surgery was recorded in detail. Clinical outcomes were assessed using the visual analogue scale (VAS) and Oswestry disability index (ODI), and the results were classified into “excellent,” “good,” “fair,” or “poor” based on the modified MacNab criteria. The incidence of hematoma with different factors was calculated, and a bar graph was used to compare the difference of the indexes related to hematoma removal between cases, and a line graph was used to reflect the trend of the outcome of each patient within 6 months to evaluate the effect of the treatment. Results A total of 461 patients with spinal stenosis who underwent Endo‐ULBD were enrolled in the study. SSEH occurred in four cases, with an incidence rate of 0.87% (4/461). All these four patients underwent decompression of multiple segments, and three of them had a history of hypertension comorbid with diabetes. Notably, one patient had a past history of hypertension and coronary artery disease and was on postoperative low molecular heparin due to lower extremity venous thrombosis. According to the conditions of the four patients, three types of treatment were used. And with timely treatment, all patients recovered well. Conclusion Despite being a minimally invasive technique, postoperative epidural hematoma remains a severe complication of Endo‐ULBD. Therefore, during percutaneous endoscopic surgery, it is essential to enhance the comprehensive perioperative management of patients with Endo‐ULBD. Signs related to postoperative hematoma must be recognized and promptly managed. If necessary, satisfactory results can be achieved by using percutaneous endoscopy along the original surgical channel to remove the hematoma.